Cholinesterase activities and oxidative stress in cattle experimentally exposed to nitrate/nitrite in cultivated pasture with different fertilization schemes - Christ R. (2018)
© 2018 Universidade Federal do Rio Grande do Sul. All rights reserved.Background: Nitrate and nitrite poisoning is associated with pasture intake that has high nitrate levels and leads to acute methemoglobinemia. Pasture may accumulate nitrate under certain conditions, such as excessively fertilized soil or environmental conditions that enhance the N absorption (rain preceded by a period of drought). After ingestion of plants, this substrate reaches the rumen and, in physiological conditions, is reduced to nitrite and afterward to ammonia. The aim of this study was to evaluate changes in cholinesterase activities and oxidative stress caused by subclinical poisoning for nitrate and nitrite in cattle fed with Pennisetum glaucum in three different fertilization schemes. Materials, Methods & Results: In order to perform the experimental poisoning, the pasture was cultivated in three different paddocks: with nitrogen topdressing (urea; group 1), organic fertilizer (group 2) or without fertilizer (group 3; control). Nitrate accumulation in forage was evaluated by the diphenylamine test. After food fasting of 12 h, nine bovine were randomly allocated to one of the experimental groups and fed with fresh forage (ad libitum) from respective paddock. In different time points from beginning of pasture intake (0, 2, 4, 6 and 9 h) heart rate and respiratory frequency were assessed, as well as mucous membrane color and behavioral changes. Blood samples from jugular vein into vials with and without anticoagulant were collected. From blood samples, serum nitrite levels, acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) enzyme activity were evaluated, as well as oxidative stress through the following parameters: levels of nitrate/nitrite (NOx), thiobarbituric acid reactive substances (TBARS) and reactive oxygen species (ROS), beyond the antioxidant system by enzyme activity measurement of catalase (CAT) and superoxide dismutase (SOD). The diphenylamine test was positive to group 1 and 2, so that the pasture presented 3.16 mg/kg, 2.98 mg/kg and 1.67 mg/kg of nitrate for group 1, 2 and 3, respectively. In addition, cows from group 1 demonstrated increased (P < 0.05) nitrite levels in serum, compared to other groups, and greater heart rate after 9 h (P < 0.05). The AChE and BChE activity in group 1 showed significant increase (P < 0.05) at 4 and 6 h (AChE), and 4 and 9 h (BChE) compared to group 3. Also, NOx levels were lower at 6 and 9 h (P < 0.05) and at 9 h (P < 0.05) for animals of group 1 and 2, respectively, when compared to group 3. Furthermore, in the group 1 levels of ROS and TBARS were significantly higher (P < 0.05) after 2 and 4 h, and 6 and 9 h compared to other groups, respectively. The CAT activity increased significantly (P < 0.05) with 2 and 4 h of the experiment, but on the other hand, decreased at 6 and 9 h in group 1. Nevertheless, the animals from group 2 presented only a significant reduction in this enzyme activity at 9 h. Furthermore, SOD activity was reduced in animals of groups 1 (P < 0.05) at 4, 6 and 9 h, compared to other groups. Discussion: It was concluded that the nitrate and nitrite poisoning by pasture intake cultivated and fertilized with urea leads to increased levels of serum nitrite, as well as the cholinesterase activity and causes oxidative stress in cattle. It is conjectured that the cholinesterase activity and oxidative stress may assist in understanding the pathophysiology of changes caused by poisoning.